2009
DOI: 10.1017/s002776300000965x
|View full text |Cite
|
Sign up to set email alerts
|

C-Convergence of Circle Patterns to Minimal Surfaces

Abstract: Abstract. Given a smooth minimal surface F : Ω → R 3 defined on a simply connected region Ω in the complex plane C, there is a regular SG circle pattern Q ǫ Ω . By the Weierstrass representation of F and the existence theorem of SG circle patterns, there exists an associated SG circle pattern P ǫ Ω in C with the combinatoric of Q ǫ Ω . Based on the relationship between the circle pattern P ǫ Ω and the corresponding discrete minimal surfaceThe theory of discrete differential geometry is presently emerging on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Also, there is a link to integrable structures via isoradial circle patterns. The approximation of conformal maps using circle patterns has been studied in [4,5,12,15,18].…”
Section: Other Convergence Results For Discrete Conformal Mapsmentioning
confidence: 99%
“…Also, there is a link to integrable structures via isoradial circle patterns. The approximation of conformal maps using circle patterns has been studied in [4,5,12,15,18].…”
Section: Other Convergence Results For Discrete Conformal Mapsmentioning
confidence: 99%
“…Next, circle patterns were used to approximate conformal mappings (see [6][7][8][9]). It was also proved that circle patterns converge to minimal surfaces (see [10,11]). Current development of research related to circle patterns can be found in [12][13][14][15].…”
Section: Introductionmentioning
confidence: 97%